Aggregation Effects on Entropy Generation Analysis for Nanofluid Flow over a Wedge with Thermal Radiation: A Numerical Investigation. (24th September 2022) - Rehman, Rabia; Wahab, Hafiz Abdul; Alshammari, Nawa; Khan, Umar; Khan, Ilyas
Abstract : The current study investigated the formation of entropy in a nanofluid flow in a wedge with thermal radiation and convective boundary conditions. Nanoparticle aggregation is also taken into consideration. The rate of heat transmission of a water-based aggregated fluid over a wedge has been investigated due to the effects of thermal radiation. A set of nonlinear differential equations governs the flow process, and these are numerically solved using a helpful approach called the Runge-Kutta-Fehlberg scheme. This method starts by breaking down the equations into a collection of first-order equations. The RK method then solves those equations. The effects on flow and heat transmission are studied using graphical analysis. Entropy generation and Bejan number changes are also graphically displayed, and the results are discussed in detail. These equations' answers were also incorporated into a dimensionless entropy generating equation. According to the findings, raising the radiation parameter and decreasing boundary convection minimize entropy generation, while nanoparticles boost entropy production.